2021
DOI: 10.21873/anticanres.14914
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Totally Implantable Central Venous Access Port-related Infection in Patients With Malignancy

Abstract: Background: We sought to identify the risk factors of totally implantable central venous access port (TICVAP)related infections in patients with malignant disease. Patients and Methods: Overall, 324 consecutive patients who received a TICVAP at our institution were retrospectively analysed. We further analysed cases of TICVAP-related complications. The risk factors for TICVAP-related infection were investigated using Cox regression hazard models. Results: With a median TICVAP duration of 268 days (range=1-1,85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…; late complications refer to complications that occur after the first use of the implantable IVAP, which mainly include catheter-related infections, thrombosis, catheter occlusion, and cardiac arrhythmia. It mainly includes catheter-related infections, thrombosis, catheter occlusion, drug extravasation, catheter displacement or fracture, catheter entrapment syndrome, superior vena cava ulceration or perforation, and infusion seat overturning [ 10 , 11 ], and catheter-related infections are the most common among them. Studies [ 12 , 13 ] reported that 46.2% of patients who had their infusion port removed during use did so because of catheter-associated infections, a rate much higher than complications such as thrombosis or other dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…; late complications refer to complications that occur after the first use of the implantable IVAP, which mainly include catheter-related infections, thrombosis, catheter occlusion, and cardiac arrhythmia. It mainly includes catheter-related infections, thrombosis, catheter occlusion, drug extravasation, catheter displacement or fracture, catheter entrapment syndrome, superior vena cava ulceration or perforation, and infusion seat overturning [ 10 , 11 ], and catheter-related infections are the most common among them. Studies [ 12 , 13 ] reported that 46.2% of patients who had their infusion port removed during use did so because of catheter-associated infections, a rate much higher than complications such as thrombosis or other dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have suggested that TPN, age over 65 years, hematological disease, and cancer with an oropharyngeal and pulmonary origin are risk factors for TIVAP-related infection [ 7 , 11 , 18 – 20 ]. Additionally, immunosuppressive status, such as neutropenia and long-term steroid usage, has been reported as a factor associated with infection [ 20 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once TIVAP-related infection was clinically suspected, TIVAP was removed and cultured following blood culture. TIVAP-related infections were classified and defined according to either of the following criteria [ 7 ]:…”
Section: Methodsmentioning
confidence: 99%
“…To identify potential factors related to CLABSI, patients’ characteristics including vital signs, laboratory data, performance status (PS), and classification of tumors were collected. White blood cell (WBC), total protein (TP), albumin, and C-reactive protein (CRP) were included as predictors of CLBASI according to the previous study ( 25 ). Data were collected the nearest day before implantation, usually 1 day before the surgery.…”
Section: Methodsmentioning
confidence: 99%